Memperkuat Kelembagaan Pemerintah Desa Untuk Menjamin Keberlangsungan Ekosistem Wilayah - Sigit Wibawanto (LP3M Universitas Putra Bangsa, 2022)
The regional ecosystem has now reached a stage that is prone to damage. This is caused by the growth of development and changes in people's lifestyles who do not care about environmental sustainability. Environmental health is now seen as a result of changing civilizations and is no longer something that needs to be controlled. This thinking now does not only occur in urban communities, but also occurs in rural communities. Involving the government as the controller and person in charge of change requires improvement from the institutional aspect, including the lowest government, namely the government. By having the ability to manage the government, it is hoped that they will be able to repair the damage to the ecosystem that has been happening in their respective regions. Strongly managed institutions regarding environmental sustainability will ensure that the regional ecosystem will be well maintained.